Kajian Grafis Uang Logam Indonesia Periode Tahun 1951-2009 - Puji Antari Rahayu; Naomi Haswanto; Alvanov Zpalanzani Mansoor (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2010)
Mostly, coins are made from metals, because of their function as an exchange device in minor transaction. In addition to another function of coins, is their value as collectible items. Both sides of coins have been keeping a great story on it, but less people are notice about this tiny forgettable stuff. Focused on Indonesian Rupiah, sorts of cultural elements and wonder of Indonesian natures are showed up on most of these coins. Equals to an archive, they captured every government's movements in some social programs on its surface. This research is going to examine and lists every details of samples, consist of 72 coin emissions in time period 1951-2009 by learning them with content analysis method and visual analysis theory. In visual communication design study, this research is trying to know further about nation's history through the story of a coin.